Pediatric Alert Score: evaluation of measurement properties - Vitória Yukari Chaves Aoki; Giselli Cristina Villela Bueno; Flávia Carvalho Pena Dias; Renata Cristina Gasparino; Daniela Fernanda dos Santos Alves (Einstein (São Paulo), 2025)
ABSTRACT Objective: To evaluate the construct validity and reliability of the Pediatric Alert Score in hospitalized children and adolescents. Methods: This methodological study included 84 children aged 0-14 years. Data were collected using three instruments: a sociodemographic and clinical characterization form, the Brazilian version Brighton Pediatric Early Warning Score, and the Pediatric Alert Score. The reliability of the Pediatric Alert Score was assessed using interobserver equivalence expressed by the intraclass correlation coefficient, and the construct validity was evaluated using Spearman's correlation analysis of the Pediatric Alert Score and the Brighton Pediatric Early Warning Score. Results: The reliability analysis of the Pediatric Alert Score revealed an intraclass correlation coefficient of 0.95 (95% confidence interval from 0.93-0.97), and the Spearman's correlation coefficient was 0.53 (p<0.0001), indicating a strong positive correlation between the instruments. Conclusion: The Pediatric Alert Score demonstrated construct validity and internal consistency in the studied sample and can be used to enhance patient safety.